Desempenho produtivo de seis variedades de mandioca (Manihot esculenta Crantz) no município de Juruti-PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The cassava crop plays a fundamental role in the Brazilian economy due to its productive, nutritious, and energetic potential. The North region, although it has the highest production volume, needs more investments in technology, such as genetic improvement, which allows for productive increases, greater resistance to pests and diseases, as well as adaptation to different edaphoclimatic conditions. This study aimed to evaluate the productive performance of six varieties of cassava (Manihot esculenta Crantz) in the municipality of Juruti in the West of the State of Pará. The experiment was conducted from December 2021 to November 2022, in a rural producer's area located in Comunidade Esperança, Km 25 of PA-257 (02°19'52" S; 55°58'40" W). The varieties used were: BRS Mari, BRS Poti, Jurará, BRS Formosa, Manivão and Coraci (local variety). The treatments were arranged in a randomized block design, factorial scheme 6 x 6, configuring 36 experimental units (EU) with repetitions. Each EU consisted of three rows of plants spaced 1.0 m apart, each row containing five plants spaced 0.8 m apart. The three plants in the central row of each EU were selected for evaluation, excluding the plants at each end. The evaluated characteristics were: number of shoots per plot (initial and final); plant height; stem diameter; number of stems per evaluated plant; root production; shoot mass and root/shoot ratio. The data were submitted to analysis of variance and means were compared using Tukey's test at 1 and 5% probability. From the results, it was verified that the genetically improved varieties presented excellent performance in terms of adaptation and productivity. The Jurará variety had the best sprouting average (14.83 plants). The Manivão variety stood out in terms of plant height (2.70 m), stem diameter (23.10 mm) and aerial part mass (1.829 kg). BRS Formosa had the highest number of stems per evaluated plant (2.17 stems/plants). BRS Poti showed the best root/shoot ratio (2.438 kg). When compared with the local variety (Coraci), it was observed that in terms of root production all are statistically equal. However, this is an unprecedented work for the municipality, serving as a basis for the implementation of new production areas, adding more knowledge about the characteristics of the varieties used, subsidizing the realization of more detailed studies.
Keywords: Manihot esculenta; Coraci; Maniva-Tapajós; Adaptação; CNPQ:: CIÊNCIAS AGRÁRIAS